PENGARUH RELIGIUSITAS, LOVE OF MONEY, MACHIAVELLIAN, DAN PENDIDIKAN ETIKA BISNIS TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI (Studi Empiris pada Mahasiswa Akuntansi Fakultas Ekonomi Universitas Islam Malang) - Safitri Yustisianingsih; Maslichah Maslichah; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACTThe purpose of this study was to determine the Effect of Religiosity, Love of Money, Machiavellian, and Business Ethics Education on the Ethical Perceptions of Accounting Students. The population in this study were students of the Accounting Study Program Faculty of Economics and Business, Malang Islamic University class of 2016. The sample was selected using purposive sampling and the calculation of the number of samples using the Slovin formula and then obtained as many as 134 students based on established criteria. This research uses multiple linear regression models. The results of this study indicate that simultaneously the variable of religiosity has a significant positive effect on the ethical perceptions of accounting students. Simultaneously the love of money variable has no effect on the ethical perceptions of accounting students. Simultaneously Machiavellian variables negatively affect the ethical perceptions of accounting students. Simultaneously the business ethics education variable has a positive effect on the ethical perceptions of accounting students.Keywords: Religiosity, Love of Money, Machiavellian, Business Ethics Education, and Ethical Perception